On the Complex and Hyperbolic Structures for the (2+1)-Dimensional Boussinesq Water Equation - Ozpinar, Figen; Baskonus, Haci Mehmet; Bulut, Hasan (Mdpi Ag, 2015)
In this study, we have applied the modified exp(-Omega(xi))-expansion function method to the (2 + 1)-dimensional Boussinesq water equation. We have obtained some new analytical solutions such as exponential function, complex function and hyperbolic function solutions. It has been observed that all analytical solutions have been verified to the (2 + 1)-dimensional Boussinesq water equation by using Wolfram Mathematica 9. We have constructed the two- and three-dimensional surfaces for all analytical solutions obtained in this paper using the same computer program.
Keywords: the modified exp (-()) -expansion function method; the (2+1)-dimensional Boussinesq water equation; complex hyperbolic function solution; exponential function solution